Are Growth Forms Consistent Predictors of Leaf Litter Quality and Decomposability across Peatlands along a Latitudinal Gradient? - Dorrepaal, Ellen; Johannes H. C. Cornelissen; Aerts, Rien; Wallén, Bo; Richard S. P. van Logtestijn (The Journal of ecology, 2005)
1 Plant growth forms are widely used to predict the effects of environmental changes, such as climate warming and increased nitrogen deposition, on plant communities, and the consequences of species shifts for carbon and nutrient cycling. We investigated whether the relationship between growth forms and patterns in litter quality and decomposition are independent of environmental conditions and whether growth forms are as good as litter chemistry at predicting decomposability. 2 We used a natural, latitudinal gradient in NW Europe as a spatial analogue for future increases in temperature and nitrogen availability. Our screening of 70 species typical of Sphagnum-dominated peatlands showed that leaf litters of Sphagnum mosses, evergreen and deciduous shrubs, graminoids and forbs differed significantly in litter chemistry and that the ranking of the growth forms was independent of the region for all litter chemistry variables. Differences among growth forms were usually larger than differences related to the environmental gradient. 3 After 8 and 20 months incubation in outdoor, Sphagnum-based decomposition beds, growth forms generally differed in decomposability, but these patterns varied with latitude. Sphagnum litters decomposed slower than other litters in all regions, again explaining its high representation in organic deposits of peatlands. Forb litters generally decomposed fastest, while the differences among the other growth forms were small, particularly at higher latitudes. 4 Multiple regression analyses showed that growth forms were better at predicting leaf litter decomposition than chemical variables in warm-temperate peatlands with a high N-load, but less so in the subarctic, low-N region. 5 Our results indicate that environmental changes may be less important in determining ecosystem leaf litter chemistry directly than are their indirect effects through changes in the relative abundance of growth forms. However, climatic and nutritional constraints in high-latitude peatlands promote convergence towards nutrient-efficient plant traits, resulting in similar decomposition rates of vascular growth forms despite differences in litter chemistry. The usefulness of the growth-form concept in predicting plant community controls on ecosystem functioning is therefore somewhat limited.